Influence of interfacial density on tribological performance of VN/TiN multilayers. (9th August 2021) - Rivera‐Chaverra, Maria J.; Escobar, Daniel; Ospina, Rogelio; Arroyave‐Franco, Mauricio; Olaya, Jhon J.; Pardo‐Trujillo, Andres; Restrepo‐Parra, Elisabeth
Abstract : A study of VN/TiN multilayers grown by direct current magnetron sputtering is presented. The systems are produced by maintaining a constant thickness of 500 nm and using three, four, or five bilayers. The coatings are initially characterized using X‐ray diffraction. We observe the formation of TiN and VN phases and obtain values of the texture and stress developed during their growth. The chemical composition of the coatings is analyzed using X‐ray photoelectron spectroscopy. A morphological analysis is carried out using atomic force microscopy, with a roughness of 1.57 nm obtained. The coefficient of friction is determined using the ball‐on‐disc method and is 0.45 for all samples. It is found that the wear rate is improved with decreasing bilayers as a consequence of the higher interfacial density (number of interfaces per total thickness). Finally, the wear mechanisms are identified as abrasive and adhesive.